2015
DOI: 10.1016/j.eneco.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Reaping the carbon rent: Abatement and overallocation profits in the European cement industry, insights from an LMDI decomposition analysis

Abstract: We analyse variations of carbon emissions in the European cement industry from 1990 to 2011, at the European level (EU 27), and at the national level for six major producers (Germany, France, Spain, United Kingdom, Italy and Poland). We apply a Log-Mean Divisia Index (LMDI) method, crossing data from three databases: the Getting the Numbers Right (GNR) database developed by the Cement Sustainability Initiative, the European Union Transaction Log (EUTL), and the Eurostat International Trade database.Our decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 34 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…They also found that the contribution of urbanization to CO 2 emissions has large variations among provinces (Ding and Li, 2017). Branger and Quirion (2015) found that CO 2 emission reductions are partly attributed to the technological improvements (i.e. to decrease the clinker share and increase in alternative fuels) and clinker trade, while the activity effect significantly contributes to the emission increase (Branger and Quirion, 2015).…”
Section: Spatial-temporal Decomposition Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the contribution of urbanization to CO 2 emissions has large variations among provinces (Ding and Li, 2017). Branger and Quirion (2015) found that CO 2 emission reductions are partly attributed to the technological improvements (i.e. to decrease the clinker share and increase in alternative fuels) and clinker trade, while the activity effect significantly contributes to the emission increase (Branger and Quirion, 2015).…”
Section: Spatial-temporal Decomposition Analysismentioning
confidence: 99%
“…Branger and Quirion (2015) found that CO 2 emission reductions are partly attributed to the technological improvements (i.e. to decrease the clinker share and increase in alternative fuels) and clinker trade, while the activity effect significantly contributes to the emission increase (Branger and Quirion, 2015). With growing interest in spatial and temporal analysis and considering the difference of performance assessment, Ang et al (2016) proposed three broad categories of decomposition analysis, namely single-country temporal analysis, multi-country temporal analysis, and cross-country analysis, while the spatial index decomposition analysis models are further divided into bilateral-region, radial-region, and multi-region models (Ang et al, 2016).…”
Section: Spatial-temporal Decomposition Analysismentioning
confidence: 99%
“…For the cement sector alone, these 'overallocation profits' are estimated at €3.5 billion. 27 EITE sectors have suffered from the crisis through reduced sales and low margins, but their financial situation would have been worse had the EU ETS not existed. Presented as a threat to competitiveness, the EU ETS has actually improved competitiveness, when defined as ability to earn.…”
Section: Carbon Leakage and Loss Of Competitiveness: What Is The Reality?mentioning
confidence: 99%
“…In the same vein, the introduction of EU ETS has not led to measurable effects for the overall economy (Dechezleprêtre and Sato, 2017). In specific cases, environmental legislation can also increase firm profits, as Branger and Quirion (2015) show for the European cement industry. Nevertheless, considering the findings of Carbone and Rivers (2017), it is conceivable that unilateral climate policy can negatively affect EITE-sectors and hence be relevant for delocalization of production capacities.…”
Section: Introductionmentioning
confidence: 99%